Lightweight mortars containing expanded polystyrene and paper sludge ash - Ferrándiz-Mas,V; Bond,T; García-Alcocel,E; Cheeseman,CR (Construction and Building Materials, 2014)
The objective of this research was to develop lightweight cement mortars with good thermal-insulation properties by incorporating expanded polystyrene (EPS) and paper sludge ash (PSA), both of which are problematic waste materials. The mortars formed had low thermal conductivity and low bulk density compared to control samples. Ground EPS produced lower thermal conductivity samples than powdered EPS. Resource efficient mortars containing up to 20% PSA, and 60% of EPS are considered suitable for use in rendering and plastering applications.